Tuberculosis research in ASEAN countries: a bibliometric analysis - cahyadin cahyadin; Ade Kartikasari Sebba; Vivin Fitriana (Berita Kedokteran Masyarakat (BKM), 2017)
Introduction. Research on TB is a fundamental key in the process to eliminate this bacterial infection as a threat to global health and the analysis of the scientific output provides valuable information related to trends in time and the epidemiology of the disease.Objective. Describing scientific output of TB research in ASEAN countries.Method. Searches were completed on August 11, 2017, using the Pubmed database, filtered by ASEAN countries. Terms related to TB were used to perform a title keyword search. The number of publications by year, research trends, top productive countries, citation analysis, and most dominant journals were analyzed by Scopus platform.Results. ASEAN countries produced 2,630 TB publications. Majority of the publications in ASEAN (63,78%) appeared in the last decade. The average annual growth rate was 9.11%. Thailand was the most productive country that contributes about 28.52% (751), followed by Singapore (432; 16.42%), Malaysia (281; 10.68%) Vietnam (231; 8.78) and Indonesia (177; 6.73%). The top two most highly cited articles were published in the Journal of Clinical Biology and The Lancet. The top three productive journals were International Journal of TB and Lung Disease (231 papers; 8.78%), Southeast Asian Journal of Tropical Medicine and Public Health (148 papers; 5.62%) and Journal of The Medical Association Thailand (112 papers; 4.25%). Top ten journal of TB contained 33.53% papers. Emerging research topics in the last years include co-infection, latent tuberculosis, interferon-gamma release tests, emigrants and immigrants, thoracic radiography, and tuberculin test.Conclusion. There was increasing research activity of TB in ASEAN region over the last decade. Thailand, Singapore, and Malaysia are the leading countries that contribute around 55.66% of total TB research in ASEAN countries.